Assessing Strategies to Enhance Instructional Delivery of Entrepreneurship Education in Tertiary Business Programmes in Bayelsa State, Nigeria - Egberi Francis, Akele; Godspower , Duoduo (American Journal of Economics and Business Management, 2024)
The research assessed methods to enhance instructional delivery in teaching entrepreneurship education within the Business Education curriculum at tertiary institutions in Bayelsa State, Nigeria. Utilizing a descriptive survey research methodology, the study addressed two research questions and tested two hypotheses at a significance level of 0.05. The participant pool comprised 89 Business Education instructors from two universities and one College of Education (Federal University Otuoke, Niger Delta University, and Isaac Jasper Boro College of Education). Given the manageable size of 89 professionals, a census sampling technique was employed to ensure the reliability and generalization of findings. Data collection involved a structured questionnaire with 23 close-ended questions, utilizing a 5-point rating scale labeled Very High Extent (VHE), High Extent (HE), Moderate Extent (ME), Low Extent (LE), and Very Low Extent (VLE) with corresponding values of 5 to 1, respectively. The questionnaire was validated by three specialists and its reliability was confirmed through the Cronbach Alpha method, achieving a reliability coefficient of 0.783. The researcher and a research assistant personally administered the questionnaires, achieving a 100% return rate. Data analysis was performed using mean and standard deviation for the research questions, and t-test statistics for hypothesis testing. A decision threshold of 3.00 on the rating scale determined the extent of agreement; means of 3.00 or above were categorized as "High Extent," and below 3.00 as "Low Extent." The null hypothesis was accepted when the computed t-value was less than the critical t-value of 1.96 at 0.05 significance level with 87 degrees of freedom, and rejected when greater. The study concluded that developing business plans and employing action-based teaching methods are effective for entrepreneurship education in Bayelsa's tertiary institutions. Therefore, the study recommended for integration of these strategies into local and national educational programmes.